Growth and development of inflorescences and fruit of Areca catechu L. (Dwarf) in Thailand - Nonthalee, Sukanya; Rukkaphan, Auttapon; Mongkong, Nimit; Ariyaphuchai, Suppaluck; Kittipaisal, Chatchai (Journal of Plantation Crops, 2026)
Areca catechu L. (dwarf-type palm) was studied to determine the morphology of the inflorescences, the growth and development of the flower and fruit, and the appropriate flower stage for pollination. Results indicated that the growth and development of male and female flowers were divided into three phases. During the first phase, the male flowers (green mixed with white) fell daily after the inflorescence emerged, while the female flowers had white sepals mixed with green and a prominent fragrance. In the second phase, the male flowers fell continuously, and the female flowers enlarged. In the third phase, the male flowers fell off the flower stalk, and the female flowers bloomed as the ideal period for pollination. At 14 days after pollination, small green fruit appeared in the inflorescence. The fruit kernel was fully formed at 98 days, with full fruit development at 182 days. The husk of the A. catechu fruit started to turn yellow at 196 days, with the fruit becoming fully ripe at 280 days.